Peningkatan Kapasitas Dosen dalam Sinkronisasi Data SINTA melalui Pelatihan dan Pendampingan Berbasis Praktik untuk Optimalisasi Profil Publikasi Ilmiah - Fakhruddin Kurnia M; Haeril Haeril; Ari Ayu; Usman Usman; A. Kartini Sari Putri D (Jurnal Akademik Pengabdian Masyarakat Ichsan Sidrap, 2025)
This community service program aimed to enhance lecturers’ capacity in managing digital academic identities through the synchronization of ORCID, GARUDA, and SINTA to optimize their scientific publication profiles. The primary issue addressed was the limited understanding and implementation of integrated researcher identity management, resulting in incomplete and inconsistent publication records. The program employed a participatory approach through hands-on training combined with direct mentoring. Participants were lecturers who had published scientific works but had not optimally synchronized their profiles across the three platforms. Data were collected through observation, documentation, and practical performance evaluation and analyzed using descriptive quantitative and qualitative methods. The results indicated that participants successfully registered and synchronized their researcher profiles, improved publication metadata, and gained practical skills in managing their digital academic identities. The hands-on mentoring approach effectively resolved technical issues encountered during the synchronization process. This program contributes to improving research information management, enhancing the visibility of lecturers’ scholarly publications, and providing a practical model for strengthening digital research competencies in higher education institutions.